THE IMPORTANCE OF DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE TEACHERS BASED ON AN INTEGRATIVE APPROACH - Barakayeva Sarvinoz To`lqunovna (Western European Studies, 2025)
The problem of improving the quality of future teachers' communicative competence, their ability to think freely, actively, independently, model the educational process, as well as the ability to independently create new ideas and technologies of education and implement them, is especially urgent in the socio-political, economic and cultural conditions that exist today
Keywords: Pedagogical process; social competence; special competence